Relentless - Childs, Tera Lynn; Deebs, Tracy (Hero agenda, 2016)
Kenna Swift has a lot on her plate--a mother who's missing, a best friend who's betrayed her, a boyfriend on trial for treason, and a new superpower she's still figuring out how to control. Not to mention she's recently learned the darkest, most dangerous secrets of the superhero world. With her team fractured and time running out, she hatches a daring plot to save those she loves the most. But soon Kenna and her friends find themselves caught in the middle of a war between the heroes who can't be trusted and the villains who don't trust anyone. When tragedy strikes, new secrets are revealed that land Kenna in the middle of a conspiracy so vast that trying to expose it might cost her more than she's willing to pay...